PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PRODUKTIVITAS BELAJAR PADA MAHASISWA PROGRAM STUDI SISTEM INFORMASI UIN SUMATERA UTARA - Sherly Pitaloka; Muhammad Irwan Padli Nasution (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study aims to analyze the effect of social media use on student learning productivity. The research subjects consisted of 60 respondents who were active students in the 5th semester of the Information Systems Study Program at UIN Sumatera Utara. The method used was simple linear regression analysis with the independent variable being the intensity of social media use and the dependent variable being learning productivity. The results of the study show that the regression equation obtained is (Y = - 0.0013X + 5.0687) with a coefficient of determination value (R^2 = 0.0022). This value indicates that the influence of social media on learning productivity is only 0.22%, while the remaining 99.78% is influenced by other factors such as motivation, discipline, and learning environment. The negative direction of the relationship indicates that the higher the use of social media, the more learning productivity tends to decline, although the effect is not significant. Thus, it can be concluded that social media does not have a significant effect on student learning productivity, but it can be a positive tool if used appropriately to support academic activities